GROUNDWATER CONSERVATION MODEL ON RECHARGE AREA OF VOLCANIC SLOPE - Murtianto, Hendro; Woei Lin, Shyang; Chen, Zue-er (IJRDO-Journal of Applied Science, 2017)
Landuse change becomes common environmental issue in each country. In developing countries,landuse change from forest to agriculture and residential area, decrease the environment quality.The impacts of landuse change to aquifer are decreasing potential groundwater, trigger for landsubsidence and changing soil ecosystem. The purpose of this study is developing model toconserve the degradation aquifer caused by landuse change. Recharge area has a big role to keepgroundwater infiltrated to aquifer zone. Research location of this research is in Merapi Volcano,an active volcano in the world. Some methods applied to conserve the aquifer, such as: buildinfiltration wells, terraces, artificial lakes and replantation. The results of this research is a modelconservation of groundwater that can improve water infiltration capacity and manage water storagein aquifer zone.